2021
DOI: 10.3390/cancers13246348
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Deregulation of Telomere-Related Genes in Newly Diagnosed Multiple Myeloma Patients

Abstract: High-risk Multiple Myeloma (MM) patients were found to maintain telomere length (TL), below the margin of short critical length, consistent with proactive overexpression of telomerase. Previously, DNA methylation has been shown as a determinant of telomere-related gene (TRG) expression and TL to assess risk in different types of cancer. We mapped genome-wide DNA methylation in a cohort of newly diagnosed MM (NDMM; n = 53) patients of major molecular subgroups, compared to age-matched healthy donors (n = 4). Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Previously, we reported that DNA methylation tightly regulates gene expression in molecular subgroups of MM [ 6 , 37 ]. Given consistent upregulation of genes encoding 4 integrins ( ITGA4 , ITGA8, ITGAE , and ITGB7 ), 2 non-integrins ( DSG2 and VCAM1 ), and 2 co-stimulatory signaling molecules ( CD28 , CD86 ) across developmental stages of the disease, we tested whether their expression levels are linked to changes in DNA methylation.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that DNA methylation tightly regulates gene expression in molecular subgroups of MM [ 6 , 37 ]. Given consistent upregulation of genes encoding 4 integrins ( ITGA4 , ITGA8, ITGAE , and ITGB7 ), 2 non-integrins ( DSG2 and VCAM1 ), and 2 co-stimulatory signaling molecules ( CD28 , CD86 ) across developmental stages of the disease, we tested whether their expression levels are linked to changes in DNA methylation.…”
Section: Resultsmentioning
confidence: 99%